PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT ETOWA PACKAGING INDONESIA DI KOTA BATAM - Pasaribu, Fitra; Siagian, Mauli (SCIENTIA JOURNAL, 2019)
Human resources are the most important asset in a company or organization, so that the company is expected to be able to manage HRM as well as possible so that there is no performance degradation for each employee. The purpose of this study was to determine the effect of motivation and work environment on employee performance. The sampling technique used in this study is the slovin formula, with data collection methods through questionnaires. Un campione totale in 115 persone provenienti from the 162 popoluzioni. Furthermore, the data that has been collected in this study is measured by many linear analyzers using SPSS 25. The results of this study show that from the test results t, it is known that for independent variables, motivation has a significant effect on employee performance, and the work environment has a significant effect on employee performance. The F test result of 77.572 is greater than f table of 3.08 with level of truth of 0.000 the alpha value of 0,05 is smaller than the level og signifincance. indicating that the motivation variable, and the work environment variable together have an effect on employee performance.